THE EFFECT OF INTERNATIONAL TRADE ON INCOME INEQUALITY: A MULTIDIMENSIONAL PANEL DATA ANALYSIS - Abdullah Takım; Sena Gültekin (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Reducing income inequality is one of the primary objectives of economic policies. Even if macroeconomic indicators such as economic growth, foreign trade, inflation, employment have improved in certain periods, regardless of the economic model applied and the level of development, income inequality at the global level, aside from decreasing, continues to be a political, social, demographic, ethical and economic problem. Because of this importance of income inequality, it is of great importance to reveal the macroeconomic factors that cause income inequality in detail. Although there is an important literature on income inequality, there are not many studies examining its relationship with international trade. While a few studies in the literature generally examine the effects of international trade on income inequality, this study, unlike others, investigates the effects of exports and imports, which constitute international trade, on income inequality. Within the scope of the study, 69 low, lower-middle, upper-middle and high income countries were examined according to the classification made by the World Bank, taking into account per capita income in the period 1995-2017. According to the results of the analysis applied using two different models, it has been concluded that, while trade openness and imports reduce income inequality, exports increase income inequality.